Toward Single Electron Nanoelectronics Using Self-Assembled DNA Structure - Tapio, Kosti; Leppiniemi, Jenni; Shen, Boxuan; Hytönen, Vesa P; Fritzsche, Wolfgang; Toppari, J. Jussi (Nano letters, 2016)
DNA based structures offer an adaptable and robust way to develop customized nanostructures for various purposes in bionanotechnology. One main aim in this field is to develop a DNA nanobreadboard for a controllable attachment of nanoparticles or biomolecules to form specific nanoelectronic devices. Here we conjugate three gold nanoparticles on a defined size TX-tile assembly into a linear pattern to form nanometer scale isolated islands that could be utilized in a room temperature single electron transistor. To demonstrate this, conjugated structures were trapped using dielectrophoresis for current–voltage characterization. After trapping only high resistance behavior was observed. However, after extending the islands by chemical growth of gold, several structures exhibited Coulomb blockade behavior from 4.2 K up to room temperature, which gives a good indication that self-assembled DNA structures could be used for nanoelectronic patterning and single electron devices.